(untitled) (Research, Society and Development, 2021)
Objective: To examine the effectiveness of using mechanical chest compression devices in reducing the risk of communicable diseases to professionals in Pre-Hospital Care. Methodology: This is a systematic review. Articles published from 2010 to 2020 in the databases Cochrane Library, ClinicalTrials, Embase, LILACS, PubMed / MEDLINE and SciELO were selected. The articles were submitted to data analysis and tabulation. Results and Discussion: 13 articles were selected, grouped into two categories: risks of communicable diseases for professionals in pre-hospital care and mechanical devices for chest compression. Studies have shown that mechanical chest compression devices (LUCAS or AutoPulse) should be used for chest compression of patients with suspected or confirmed communicable diseases, being the primary indication and should be used as soon as available. Conclusion: The use of mechanical chest compression devices reduces the risk of diseases communicable to professionals in pre-hospital care during CPR. However, there is still an urgent need for more research that seeks to contribute to reducing the infection rate of these professionals.